2012
DOI: 10.1124/mol.111.076539
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus 16 E6 RNA Interference Enhances Cisplatin and Death Receptor-Mediated Apoptosis in Human Cervical Carcinoma Cells

Abstract: In cervical cancer, the p53 and retinoblastoma (pRb) tumor suppressor pathways are disrupted by the human papilloma virus (HPV) E6 and E7 oncoproteins, because E6 targets p53 and E7 targets pRb for rapid proteasome-mediated degradation. We have investigated whether E6 suppression with small interfering RNA (siRNA) restores p53 functionality and sensitizes the HPV16-positive cervical cancer cell line SiHa to apoptosis by cisplatin, irradiation, recombinant human tumor necrosis factor-related apoptosis-inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 41 publications
0
29
1
Order By: Relevance
“…These findings indicate that intrinsic p53 expression is suppressed by HPV E6 and that knockdown of E6 is essential for p53 expression. However, additional treatments were required to induce apoptosis of cervical cancer cells (Hougardy et al, 2006;Tan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that intrinsic p53 expression is suppressed by HPV E6 and that knockdown of E6 is essential for p53 expression. However, additional treatments were required to induce apoptosis of cervical cancer cells (Hougardy et al, 2006;Tan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of RNAi to inhibit the expression of E6/E7 genes has been studied intensively (Alvarez-Salas, BenitezHess, & DiPaolo, 2003;Butz et al, 2003). Furthermore, several studies revealed that treatment of cancer with siRNA was able to enhance the effect of anti-tumor drugs such as cisplatin (Tan et al, 2012), doxorubicin, and gemcitabine (Koivusalo, Krausz, Helenius, & Hietanen, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…E7 is responsible for pRb degradation, a negative regulator of the cell cycle, leading to S-phase entry, viral replication and maintenance [6]. E6 and E7 inhibition or knockdown is a promising therapeutical strategy to act on cancer cells to potentially induce cell death or growth arrest [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency in vivo could be improved by transferring the miRNA expression cassettes into conditionally replicative adenoviruses (CRAd) which should allow a better killing of tumor cells and an improved vector dissemination[20]. Another possibility would be the use of a combinatorial treatment with Ad18_2 and Cisplatin[8]. Very recently we designed a high affinity bivalent ligand able to bind specifically to E6 of all high risk HPV[21].…”
mentioning
confidence: 98%